Compton double ionization of the helium atom: Can it be a method of dynamical spectroscopy of ground state electron correlation?. (February 2022) - Chuluunbaatar, O.; Houamer, S.; Popov, Yu.V.; Volobuev, I.P.; Kircher, M.; Dörner, R.
Highlights: A new method of dynamical spectroscopy. Compton ionization of atoms. Formulating conditions for new experiments. Abstract: Recent experiments on single and double ionization of atoms by Compton scattering potentially open the door to establishing new methods of dynamical spectroscopy complementing the well-known methods like (e, 2e) and (e, 3e) spectroscopy. In this paper we explore the possibility to use double ionization of the helium atom by Compton scattering as a tool for direct spectroscopy of electron-electron correlations. For rather high photon energies of a few dozens of keV, a non-relativistic theoretical description of the process and the Kramers-Heisenberg-Waller approximation can be consistently used with a high computational efficiency.